On-farm methane measurements during milking correlate with total methane production by individual dairy cows - Garnsworthy, P.C.; Craigon, J.; Hernandez-Medrano, J.H.; Saunders, N. (American Dairy Science Association, 2012)
The objective of this study was to investigate whether measurement of methane emissions by individual dairy cows during milking could provide a useful technique for monitoring on-farm methane emissions. To quantify methane emissions from individual cows on farm, we developed a novel technique based on sampling air released by eructation during milking. Eructation frequency and methane released per eructation were used to estimate methane emission rate. For 82 cows, methane emission rate during milking increased with daily milk yield (r=0.71), but varied between individuals with the same milk yield and fed the same diet. For 12 cows, methane emission rate recorded during milking on farm showed a linear relationship (R2=0.79) with daily methane output by the same cows when housed subsequently in respiration chambers. For 42 cows, the methane emission rate during milking was greater on a feeding regimen designed to produce high methane emissions, and the increase compared with a control regimen was similar to that observed for cows in respiration chambers. It was concluded that, with further validation, on-farm monitoring of methane emission rate during milking could provide a low-cost reliable method to estimate daily methane output by individual dairy cows, which could be used to study variation in methane, to identify cows with low emissions, and to test outcomes of mitigation strategies.